COVID-19 and addiction. Issue 5 (September 2020) - Dubey, Mahua Jana; Ghosh, Ritwik; Chatterjee, Subham; Biswas, Payel; Chatterjee, Subhankar; Dubey, Souvik
Abstract: Background and aims: 2019-coronavirus disease (COVID-19) is causing insurmountable psychosocial impact on the whole mankind. Marginalized community, particularly those with substance use disorders (SUD), are particularly vulnerable to contract the infection and also likely to suffer from greater psychosocial burden. This article analyses the intricate bi-directional relationship between COVID-19 and addiction. Methods: Pubmed and Google Scholar are searched with the following key terms- "COVID-19", "SARS-CoV2", "Pandemic", "Addiction", "Opioid", "Alcohol", "Smoking", "Addiction Psychiatry", "Deaddiction", "Substance use disorders", "Behavioral addiction". Few newspaper reports related to COVID-19 and addiction have also been added as per context. Results: People with SUD are at greater risk of worse COVID-19 outcome. There is surge of addictive behaviors (both new and relapse) including behavioral addiction in this period. Withdrawal emergencies and death are also being increasingly reported. Addicted people are especially facing difficulties in accessing the healthcare services which are making them prone to procure drugs by illegal means. Conclusion: COVID-19 and addiction are the two pandemics which are on the verge of collision causing major public health threat. While every effort must be taken to make the public aware of deleterious effects of SUD on COVID-19 prognosis, the resumption of deaddiction services and easier accessibility of prescription drugs are needs of the hour. Highlights: Addiction and COVID-19 fuel each other to cause a global public health threat. Resumption of deaddiction service and relaxation of accessibility of prescription drugs are needed. Psychiatrists must be prepared for imminent hike in withdrawal symptoms and addictive behaviors.